Yolk-sac carcinoma mimicking sacrococcygeal teratoma in an infant - Evance Salvatory Rwomurushaka; Alex Mremi; Jay Lodhia (Radiology Case Reports, 2025)
Extragonadal germ cell tumors (GCTs) are rare, accounting for 1% to 5% of all GCTs, with malignant sacrococcygeal yolk sac tumors (SCYSTs) being part of this uncommon subset. These tumors primarily occur in children and young adults and are known for their aggressive behavior, necessitating early diagnosis and prompt treatment. In this case report, we present the case of an 8-month-old female who presented with mild abdominal distension and a 3-week history of difficulty passing urine. Imaging revealed a pelvic mass originating from the coccyx, compressing the urinary bladder. The mass was surgically excised, and histopathological analysis confirmed a malignant yolk sac tumor with positive margins. The patient received adjuvant chemotherapy postsurgery. Despite treatment, follow-up scans showed residual tumor tissue, leading to a second tumor resection. Surveillance was continued using Alpha Fetoprotein (AFP) levels as a marker, which revealed a relapse of the tumor. Subsequent imaging confirmed a growing tumor, and the patient was scheduled for second-line chemotherapy. Management of SCYSTs is complex and requires a multidisciplinary approach, including surgeons, oncologists, radiologists, and pathologists. While relapse is rare, it poses a significant challenge for treatment, underscoring the need for clear and updated guidelines for managing relapsed cases.